Nietzsche e o "eterno-feminino": a posição da mulher e o diagnóstico nietzschiano da cultura - Paulo, Vinicius Souza De [UNIFESP] (2020)
This dissertation aims to analyze the position of women in Friedrich Nietzsche's thought, with regard to the diverse metaphors, images, typologies and mythical references of women, which appear in the nietzschean work expressing a positive value of women, in their relationship with the acid criticisms directed at the modern woman, at the feminine expressions of modern culture, which extend even to the feminist movements of emancipation of modernity. Through a contrast between the positive and negative aspects of women that permeate the work of Nietzsche, it is possible to see that the position of women in nietzschean thought has a direct relationship with his critique of modern culture as an expansion of platonic/christian values that support the basis of the nihilistic condition of modernity. In this sense, the positive images of women, in addition to denouncing all the ascetic idealism prevailing in modern women, which demean the body and instincts, are consequently an expression of the values that Nietzsche seeks to restore, not only in culture, but also in the image of human, as an yet undetermined animal, going beyond fixed identities, idealistic, metaphysical, substantial conceptions of the human, evidenced in the decadent movements of modernity, valuing a dionysian vision of life affirmation.